2009
DOI: 10.1038/nphys1232
|View full text |Cite
|
Sign up to set email alerts
|

Control of a magnetic Feshbach resonance with laser light

Abstract: The capability to tune the strength of the elastic interparticle interaction is crucial for many experiments with ultracold gases. Magnetic Feshbach resonances 1,2 are widely harnessed for this purpose, but future experiments 3-8 would benefit from extra flexibility, in particular from the capability to spatially modulate the interaction strength on short length scales. Optical Feshbach resonances 9-15 do offer this possibility in principle, but in alkali atoms they induce rapid loss of particles due to light-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
180
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(188 citation statements)
references
References 33 publications
(43 reference statements)
6
180
2
Order By: Relevance
“…Optical Feshbach resonances are known to incur excess heating due to spontaneous emission from the excited state, and that could be detrimental for realizing many-body localization. To mitigate this effect, we suggest to use a scheme in which the light couples the bound Feshbach molecular state to an excited molecular state off-resonantly [42,43]. Using this scheme the heating time can be as long as 10ms [44], which is about 50t −1 h [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Optical Feshbach resonances are known to incur excess heating due to spontaneous emission from the excited state, and that could be detrimental for realizing many-body localization. To mitigate this effect, we suggest to use a scheme in which the light couples the bound Feshbach molecular state to an excited molecular state off-resonantly [42,43]. Using this scheme the heating time can be as long as 10ms [44], which is about 50t −1 h [9].…”
mentioning
confidence: 99%
“…[3,27]. We proposed a realization of this model in cold atom experiments using spatially resolved optical Feshbach resonances [42,43]. In this model, many-body localization follows from fragmentation of particles into slow and fast species (doublons and singlons), which is a result of the strong interactions.…”
mentioning
confidence: 99%
“…Previous studies have shown that FRs can be modified either by dressing the molecular bound state in the closed channel [2][3][4][5][6][7][8][9], or by coupling different atomic states in the open channel [10][11][12][13][14]. Under these situations, the resonance position as well as the atomic scattering length can be tuned by additional parameters.…”
mentioning
confidence: 99%
“…Efforts toward achieving OFR in quantum gases have made significant progress [15][16][17][18][19][20][21][22][23][24][25][26][27][28] but have encountered two major obstacles. First, in previous experiments OFR has limited the quantum gas lifetime to the millisecond time scale [24,26,27] due to optical excitation to molecular states.…”
mentioning
confidence: 99%
“…Assuming the molecular and atomic magnetic moments differ μ m ≠ 2μ a , the vector light shift can bring the molecular states closer to the scattering state, inducing a resonant atom-molecule coupling. Optical shifts of a magnetic Feshbach resonance have been observed using specific bound-to-bound transitions [25][26][27][28] and recently using a far-detuned laser [38]. Since our scheme does not rely on proximity to any atomic or molecular transitions, the lifetime is only limited by the one-body off-resonant scattering rate.…”
mentioning
confidence: 99%